Identifikasi Miskonsepsi Materi Upaya Pelestarian dan Keseimbangan Alam Kelas V SDN Bendogerit 1 - Sholiahtuzumna Putri Permadani; Jihan Dewi Nur Aini; M Anas Thohir; Sholiahtuzumna Putri Permadani; Jihan Dewi Nur Aini (Universitas Negeri Malang, 2022)
Abstract: Misconception is one of the cause of low score for the students’ subject or lessons. Then, the teacher is one of the factor of students’ misconception. The aims of the research is to describe the misconception among the students of the Fifth Class SDN Bendogeerit 1, particularly the their misconception of sciences relating to effort in preservation and natural balance. The participants of research are 9 men and 10 girls in the fifth grade at SDN Bendogerit 1. The methode used in the research was descriptive quantitative. The data was gained through multiple choice test that using the answering sheet certainty of respone index (CRI) and the sample was 19 students. The result of research was: 1) misconception was occuring among the fifth grade students; 2) misconception was not influenced by the difficulties of questions level (misconception was occurred in any difficulties levels); 3) cognitif levell that mostly appeared the misconception was C2 (understanding); 4) the students which the abilities in low categories mostly having the misconception. Some advices of researcher, such as: the teachers must be change their low qualities of style and method learning upgrading the learning process (meaningful learning) through the constructive process in the form of active learning using the available media. Abstrak: Miskonsepsi merupakan salah satu penyebab rendahnya nilai pada suatu mata pelajaran pada siswa. Salah satu faktor miskonsepsi pada siswa adalah guru. Tujuan dari penelitian ini adalah untuk mendeskripsikan miskonsepsi yang terjadi pada siswa kelas V SDN Bendogeerit 1, khususnya pada mata pelajaran IPA tentang upaya pelestarian dan keseimbangan alam. Partisipan pada penelitian kali ini terdiri dari siswa 9 laki-laki dan 10 perempuan kelas V SDN Bendogerit 1.Metode penelitian yang digunakan adalah deskriptif kuantitatif. Data penelitian diperoleh melalui tes pilihan ganda dengan lembar jawaban certainty of respone index (CRI) dengan sampel berjumlah 19 siswa. Temuan dari penelitian ini : 1) Miskonsepsi telah terjadi pada siswa SD kelas 5 di beberapa konsep yang diteliti; 2) Miskonsepsi, tidak bergantung pada tingkat kesukaran soal (miskonsepsi bisa terjadi tingkat kesukaran apa saja); 3) Jenjang kognitif yang banyak menimbulkan miskonsepsi adalah C2 (pemahaman); 4) Siswa dengan kemampuan kategori rendah paling banyak mengalami miskonsepsi. Beberapa saran dari peneliti, diantaranya : Guru diharapkan dapat merubah pola dan gaya mengajar berkualitas rendah ke pembelajaran yang bermakna (meaningful learning) melalui proses-proses yang konstruktif melalui bingkai pembelajaran aktif yang dibantu penggunaan media yang baik.